2013
DOI: 10.1139/cjz-2012-0183
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand mudsnails (Potamopyrgus antipodarum) in Boulder Creek, Colorado: environmental factors associated with fecundity of a parthenogenic invader

Abstract: New Zealand mudsnails (Potamopyrgus antipodarum (Gray, 1853)) are non-native snails that are increasingly spreading in freshwater systems in North America. Most invasive populations are parthenogenic and threaten native freshwater diversity. We observed variability of P. antipodarum fecundity each month for 16 months at a recently invaded site in Boulder Creek, Colorado. We collected 100 snails each month and dissected them to count embryos in the brood sac. We used a general linear model analysis to examine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…Our data suggest that shell size varies as a function of phenotypic plasticity. Like previous studies, we demonstrated a direct, positive association between size and fecundity in female P. antipodarum (McKenzie et al., ). Several environmental factors affected size or fecundity directly, but only two of these factors, flow and turbidity, had an effect on brood size in interaction with size.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data suggest that shell size varies as a function of phenotypic plasticity. Like previous studies, we demonstrated a direct, positive association between size and fecundity in female P. antipodarum (McKenzie et al., ). Several environmental factors affected size or fecundity directly, but only two of these factors, flow and turbidity, had an effect on brood size in interaction with size.…”
Section: Discussionsupporting
confidence: 90%
“…Any embryos were then removed and the head of each snail placed back into 96% ethanol to be sent to LGC Genomics (http://www.lgcgroup.com) for DNA extraction, mtDNA sequencing, and SNP genotyping. We assumed that embryo counts were comparable across samples because all snails were collected during the summer months, the presumptive reproductive peak (McKenzie et al., ; Schreiber, Glaister, Quinn, & Lake, ). Because infection status (and male vs. female status) can affect shell shape and size in P. antipodarum (e.g., Lagrue et al., ; Levri et al., ), we also determined whether macroparasites were present in the body cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Females were reproductively mature at shell height from 2.5 to 3.0 mm, with up to 74 embryos in the largest females. These results are also consistent with observations for other introduced populations, which mature at size between 2.5 and 3.5 mm, and have maximum brood size ranging from 60 to 89 embryos (e.g., Strzelec & Serafinski, 1996;Gaino et al, 2008;McKenzie et al, 2013).…”
Section: Temporal Fluctuations Of Abundance and Fecundity Of P Antipsupporting
confidence: 80%
“…The lack of sexual reproduction is consistent with what is seen for introduced P. antipodarum from Europe, Australia, and America, where males are rare or completely absent (e.g., Wallace, 1978Wallace, , 1985Hughes, 1996;Schreiber et al, 1998;Gaino et al, 2008;McKenzie et al, 2013;Collado, 2014). increased from March to May in each year, and also increased with snail size, as previously demonstrated (e.g., Winterbourn, 1970;Gérard & Poullain, 2005;Gaino et al, 2008;McKenzie et al, 2013).…”
Section: Temporal Fluctuations Of Abundance and Fecundity Of P Antipsupporting
confidence: 71%
See 1 more Smart Citation